A community for students. Sign up today!
Here's the question you clicked on:
 0 viewing
 2 years ago
For which value on the real constant a were the line L intersects the point (4,1,3), with the direction vector (3,a,2), the plane \[(x,y,z)=(1+t2s, 2t+s,1+3t+as), t,s \in \mathbb{R}\] in one point.
 2 years ago
For which value on the real constant a were the line L intersects the point (4,1,3), with the direction vector (3,a,2), the plane \[(x,y,z)=(1+t2s, 2t+s,1+3t+as), t,s \in \mathbb{R}\] in one point.

This Question is Closed

amistre64
 2 years ago
Best ResponseYou've already chosen the best response.2it sounds doable, but its hard to make out what its actually asking for

frx
 2 years ago
Best ResponseYou've already chosen the best response.0New formulation: For which values of the real constant a does the line L ( L goes trough the point (4,1,3) and has the direction vector (3,a,2)) intersect the plane \[(x,y,z)=(1+t2s, 2t+s,1+3t+as), t,s \in \mathbb{R}\] in one point.

amistre64
 2 years ago
Best ResponseYou've already chosen the best response.2we might wanna try to redefine the plane in a format thats easier to parse. (x,y,z)=(1+t−2s,2t+s,1+3t+as),t,s x = (1+t−2s,2t+s,1+3t+as) y = t z = s is there a way to construct that as: a(xxo)+b(yyo)+c(zzo)=0 ??

amistre64
 2 years ago
Best ResponseYou've already chosen the best response.2the line equation parts are x = 4 + 3n y = 1 + an z = 3 +2n

frx
 2 years ago
Best ResponseYou've already chosen the best response.0I think it's x=1+t2s, y= 2t+s, z=1+3t+as and the t,s is just to say that thet are Real

amistre64
 2 years ago
Best ResponseYou've already chosen the best response.2hmm, then we might be able to use x and y to solve for n, and use n to solve for a ... is my idea

frx
 2 years ago
Best ResponseYou've already chosen the best response.0\[(x,y,z)=(1+t2s),2t+s, 1+3t+as)\] \[x=1+t2s\] \[y=2t+s\] \[z=1+3t+as\] where \[t,s \in \]

amistre64
 2 years ago
Best ResponseYou've already chosen the best response.2x = 4 + 3n y = 1 + an z = 3 +2n and x = 1 + t  2s y = 0 + 2t + s z = 1 + 3t + as (3 + t  2s)/3 = n (1 + 2t + s)/a = n (2 + 3t + as)/2 = n

amistre64
 2 years ago
Best ResponseYou've already chosen the best response.2(3 + t  2s)/3 = n (1 + 2t + s)/a = (3 + t  2s)/3 (2 + 3t + as)/2 = (3 + t  2s)/3 a = (3 + 6t + 3s)/(3 + t  2s) 6 + 9t + 3s(3 + 6t + 3s)/(3 + t  2s) = 6 + 2t  4s 7t +4s + 3s(3 + 6t + 3s)/(3 + t  2s) = 0 21t + 7t^2  14ts 12s + 4st  8s^2 + 9s +18st + 9s^2 = 0 21t + 7t^2 21s + s^2 +8st = 0 7t^221t + s^2 21s+8st = 0 needs more shuffling, but i believe thats the right idea to take

frx
 2 years ago
Best ResponseYou've already chosen the best response.0I think I get the idea, will have to spend some time on i tough, thank you for your help! :)
Ask your own question
Ask a QuestionFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.